2019
DOI: 10.1002/acr.23731
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Fibromyalgia: Disagreement Between Fibromyalgia Criteria and Clinician‐Based Fibromyalgia Diagnosis in a University Clinic

Abstract: ObjectiveRecent studies have suggested that fibromyalgia is inaccurately diagnosed in the community, and that ~75% of persons reporting a physician diagnosis of fibromyalgia would not satisfy published criteria. To investigate possible diagnostic misclassification, we compared expert physician diagnosis with published criteria.MethodsIn a university rheumatology clinic, 497 patients completed the Multidimensional Health Assessment Questionnaire (MD‐HAQ) and the 2010 American College of Rheumatology preliminary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 40 publications
1
50
1
Order By: Relevance
“…Some other studies have also looked at the concordance issue. In a university rheumatology clinic, 50.4% of 104 consecutive patients with a fibromyalgia clinical diagnosis also satisfied fibromyalgia criteria, and 24.3% of 121 criteria-positive patients received a clinical diagnosis of fibromyalgia (22). Agreement beyond chance was only fair: kappa 0.41.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have also looked at the concordance issue. In a university rheumatology clinic, 50.4% of 104 consecutive patients with a fibromyalgia clinical diagnosis also satisfied fibromyalgia criteria, and 24.3% of 121 criteria-positive patients received a clinical diagnosis of fibromyalgia (22). Agreement beyond chance was only fair: kappa 0.41.…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear boundaries between what is and what is not FM (32). A number of studies have found substantial discordance between patient-reported diagnosis of FM and assessment using FM criteria (33)(34)(35). While there are many potential reasons for such discordance, uncertainty related to criteria may be one contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study of about 500 patients under diagnosis of FM, revealed that 24.3% satisfied the FM criteria, while 20.9% received a clinician International Classification of Diseases (ICD) diagnosis of FM, with a 79.2% agreement between clinicians and criteria. The conclusions of this study pointed out a disagreement between ICD clinical diagnosis and criteria-based diagnosis of FM, calling into question meaning of a FM diagnosis, the validity of physician diagnosis and clinician bias [ 24 ].…”
Section: Diagnosismentioning
confidence: 99%